Queer -activism and intersectionality? A discourse analysis of queer -political subject formations in the problematization of 'race' - Vogler, Tanja (Social movement studies, 2025)
Queer and intersectional perspectives play an important role in activism and academia and are critical of a collective 'we' that is arranged around a (single-issue) identity. However, queer sexual politics are still a side of white theory production, especially in the German-speaking world. This study explores how the current queer political subject in the German-speaking world is constituted in the 'problematization' of racism based on a poststructuralist critique of the subject. Against the backdrop of the shared but slightly different critique of identity politics from queer and intersectional perspectives, it also looks at the role intersectionality plays in these queer problematizations of racism. To that end, following Foucault and Jäger, discourse analysis was conducted on materials produced by five German-speaking queer-activist organizations between 2010 and 2016. This study presents the results of the analysis of two representative discourse fragments; in both discourse fragments, a more open queer political subject is constituted in the problematization of 'race' by referring in slightly different ways to intersectional critiques, but also to the concept of precarity.